Management of post-harvest spoilage of kinnow fruits by pre-harvest spraying of fungicides - and R.B. GAUR, R.N. SHARMA*, R.P. MAHARSHI1 (Indian Phytopathology, 2010)
Studies were conducted (2004-05 to 2005-06) on post-harvest rotting (spoilage) of kinnow fruits at Sriganganagar(Rajasthan). Surveys of cold storages revealed 34 to 38 per cent of post-harvest rotting in kinnow fruits. Core rot, stem-end rot, green mould rot and blue mould rot were the most destructive rots sharing 80 to 90 per cent of the total post-harvest rotting. During the storage under cold store conditions (Temp. 5 ± 1 °C and R.H. 85-90%), the fruits harvested from the plants treated with chemical or fungicidal sprays exhibited significantly less rotting in comparison to the fruits of untreated control plants. Prochloraz proved most effective fungicide in checking the post-harvest fruit rotting followed by Carbendazim provided complete protection to the fruits from infection up to 30 and 15 days of storage respectively. Minimum spoilage of 7.23 and 9.45 per cent was recorded in Prochloraz and Carbendazim respectively after 60 days of storage under cold store conditions. Eleven fungi were found associated with rotted fruits during the storage. Alternaria alternata, Botryodiplodia theobromae, Penicillium digitatum and P. italicum were most prominent to cause more than 60 per cent spoilage of the total fruit spoiled during the storage.